Thyroid cancer cell lines: Critical models to study thyroid cancer biology and new therapeutic targets - Schweppe, Rebecca E. (Frontiers in Endocrinology, 2012)
Thyroid cancer is the most common endocrine malignancy and the incidence is rising. Currently, there are no effective treatments for patients with advanced forms of thyroid cancer. Anaplastic thyroid represents the most severe form of the disease with 95% mortality at 6 months. It is therefore critical to better understand the mechanisms involved in thyroid cancer development and progression in order to develop more effective therapeutic strategies. Cell lines derived from thyroid tumors represent a critical tool to understand the oncogenic mechanisms driving thyroid cancer, as well as preclinical tools to study the efficacy of new therapies in vitro and in vivo. For thyroid cancer, the development of new therapies has been hampered by the lack of thyroid cancer cell lines in the widely used NCI-60 panel which has been used to screen over 100,000 anti-cancer drugs. In addition, the recent discovery that 20 out of 40 existing thyroid cancer cell lines are either redundant or misidentified with cell lines of other tissue lineages has further hampered progress in the field. Of the available cell lines, 23 were identified as unique and presumably of thyroid origin based on the expression of thyroid-specific genes. Thus, there is a great need for validated thyroid cancer cell lines representing different stages of disease in addition to distinct oncogenic mutations. New, authenticated thyroid cancer cell lines are beginning to be developed, adding to the tools available to study genes and pathways important for thyroid cancer pathogenesis. In summary, the use of validated thyroid cancer cell lines that closely recapitulate disease is critical for the discovery of new drug targets and ultimately new therapies.